Sanogenic behavior in the context of healthy lifestyle - N. D. Tvorogova (Сеченовский вестник)
One of the most important areas of health promotion is the stimulation of positive changes in people's behavior and lifestyle. It is time to join the efforts of various specialists in health schools (in individual and public health management programs) to maintain individual physical, mental, social and spiritual well-being. Realizing the importance of psychology in the prevention of non-communicable diseases, the Ministry of Healthcare of the Russian Federation decided to create multidisciplinary rehabilitation teams, which should include medical psychologists. In the article Doctor of Psychological Sciences, N.D. Tvorogova, who researched into various aspects of health psychology for several decades, shares the results of her theoretical and empirical studies.